The Historical and Cultural Layers in the Travelogues of Altaf Yousafzai - Barkat, Misbah; Parveen, Azra (Makhz (Research Journal), 2025)
Travel is not merely a movement across geographical boundaries, but a journey of self-realization infused with civilizational and historical consciousness. In Urdu literature, the tradition of travel writing has never been confined to physical observations alone; rather, it has encompassed layers of culture, history, psychology, society, and identity. Dr. Altaf Yousafzai’s travelogues stand as a significant and intellectual contribution to this modern tradition. His travel narratives Thailand ke Rang, Neel ke Sang, and Bekhaal Hindosh Bakhsham are not mere tourist accounts, but thoughtful engagements with intercultural dialogue, historical memory, and the inner psyche of a Muslim traveler. This paper, through selected textual references, demonstrates how Altaf Yousafzai crafts a symbolic and reflective narrative that bridges the past and the present, East and West, faith and modernity. His prose reveals not only a personal lens but also a broader civilizational commentary, reviving historical consciousness and inviting intellectual reflection. For him, history is not a static recollection of the past but a living framework for interpreting the present and shaping the future.